History as an Instrument of Peace Education: An Analysis of History Learning at SD Negeri 10 Takengon in the Post-Conflict Context of Aceh - Amanda, Arizka; Fajri, Ahmad; Adawiyah, Radiatul; Sopacua, Jems (Universitas Pattimura, 2025)
This study aims to examine the implementation of history-based peace education at SDN 10 Bebesen, Central Aceh, with a focus on the challenges faced by teachers and its impact on students. The method used is a qualitative approach through in-depth interviews with history teachers, education supervisors, and students. The results show that although history-based peace education has been introduced, its implementation remains limited by a curriculum that focuses more on historical events than on reconciliation and conflict resolution. Teachers face difficulties in linking peace education with historical events due to a lack of adequate training and resources. On the other hand, students demonstrate an understanding of peace values but struggle to apply them in daily life, especially those from families affected by conflict. This study concludes that enhancing teacher capacity through more specific training and the application of more interactive teaching methods is essential to improving the effectiveness of history-based peace education. Future research is expected to broaden the sample scope and explore project-based approaches to optimize the implementation of peace education in elementary schools.